PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT SINAR SURYA SENTOSA SEJAHTERA TANGERANG SELATAN - Subhan, Muhammad; Rizka Akbar, Irfan (Journal of Research and Publication Innovation, 2024)
This research aims to analyze Work Discipline and Work Motivation on Employee Performance partially and simultaneously. The population in this study were employees of PT Sinar Surya Sentosa Sejahtera with a sample size of 68 people. The analytical method used is Descriptive Quantitative Analysis. The instrument used is a questionnaire to collect data from the variables Work Discipline, Work Motivation and Employee Performance. The data analysis techniques used are Vasility Test, Reliability Test, Normality Test, Molticoliniarity Test, Heteroscedasticity Test, Multiple Linear Regression Analysis Test, Multiple Correlation, Determination Coefficient, T-Test, and F Test. The results of the research show that Linear Analysis values can be obtained. Multiple Y = 0.766 + 0.767X1 + 0.216X2, Multiple Correlation Coefficient of 0.811, and Determination Coefficient of 0.686. Then the value of tcount < ttable or (0.1666 < 1.67109), this is also strengthened by the significance value of 0.869 > 0.05. This shows that there is a positive and significant influence between Work Discipline (X1) on the Employee Performance of PT Sinar Surya Sentosa Sejahtera. Meanwhile, the results of the t test on This shows that there is a positive and significant influence between Work Motivation (X2) on PT Sinar Surya Sentosa Sejahtera Employee Performance. Then the F test results can be obtained with a value of Fcount > Ftable or (71.082 > 3.140) and is strengthened with a sig of 0.000 < 0.05. This shows that there is a positive and significant influence between Work Discipline (X1) and Work Motivation (X2) on Employee Performance (Y) of PT Sinar Surya Sentosa Sejahtera.